2018
DOI: 10.7458/spp20199015528
|View full text |Cite
|
Sign up to set email alerts
|

Atitudes face à divisão do trabalho familiar em Portugal em 2002 e 2014: mudanças e continuidades

Abstract: Este artigo pretende analisar a evolução das atitudes face à divisão conjugal do trabalho em Portugal, entre 2002 e 2014. Um dos objetivos centrais é o de aferir em que medida a evolução observada corresponde a uma modernização das atitudes. Avaliam-se igualmente as hipóteses de uma complexificação dos padrões atitudinais ou, em alternativa, de uma cristalização em torno de padrões atitudinais dicotómicos. Para tal foi efetuada uma análise comparativa das atitudes dos portugueses aferidas nos módulos Família e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
6
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 0 publications
0
6
0
Order By: Relevance
“…On average, 37% of women spend at least one hour per day caring for family members, compared with 28% of men. For couples with children, this proportion increases to 87% of Correia (2019) showed that, despite the perception among women that they do more work than would be fair, and of men that they do less, there were significant changes in indicating a recognition of a more egalitarian division of housework.…”
Section: Pre-pandemic Division Of Paid and Unpaid Workload Among Mixe...mentioning
confidence: 96%
See 1 more Smart Citation
“…On average, 37% of women spend at least one hour per day caring for family members, compared with 28% of men. For couples with children, this proportion increases to 87% of Correia (2019) showed that, despite the perception among women that they do more work than would be fair, and of men that they do less, there were significant changes in indicating a recognition of a more egalitarian division of housework.…”
Section: Pre-pandemic Division Of Paid and Unpaid Workload Among Mixe...mentioning
confidence: 96%
“…also concluded that the sharing of household chores and care work within families in Portugal remains largely asymmetrical from a gender perspective, with women spending on average 4 hours and 23 minutes on unpaid work on weekdays, 1 hour and 45 minutes/day more than men. This trend is reinforced on weekends, when the authors estimate that women spend 12 hours (half a day) more than men doing unpaid work.While data on time spent on paid and unpaid work reported by men and women provide a relatively objective view of inequalities, analysing satisfaction in the division of unpaid work offers valuable insights into subjective gender role norms based on individuals' cultural and ideological values that enable the perpetuation of this issue(Amâncio & Correia 2019;Cunha & Atalaia 2019;Ramos, Rodrigues, & Correia 2019). In an analysis of the 2002 and 2014 International Social Survey Program (ISSP) of housework sharing arrangements between Portuguese men and women, Amâncio and…”
mentioning
confidence: 99%
“…While data on time spent on paid and unpaid work reported by men and women provide a relatively objective view of inequalities, analysing satisfaction in the division of unpaid work offers valuable insights into subjective gender role norms based on individuals' cultural and ideological values that enable the perpetuation of this issue (Amâncio & Correia 2019;Cunha & Atalaia 2019;Ramos, Rodrigues, & Correia 2019). In an analysis of the 2002 and 2014 International Social Survey Program (ISSP) of housework sharing arrangements between Portuguese men and women, Amâncio and Correia (2019) showed that, despite the perception among women that they do more work than would be fair, and of men that they do less, there were significant changes in indicating a recognition of a more egalitarian division of housework.…”
Section: Pre-pandemic Division Of Paid and Unpaid Workload Among Mixe...mentioning
confidence: 99%
“…At the level of social representation, the essentialist vision of mothers and mothering and child-centered familism persisted, but they also connected with the wish for greater male involvement in care. This hybrid attitudinal pattern characterizes Portuguese society, varying according to sex, generation, and social class (Aboim, 2010;Gouveia & Widmer, 2014;Ramos et al, 2019).Recent research revealed the coexistence of three main post-divorce custody regimes in Portugal: sole maternal custody; joint legal custody (introduced by the Law 61/2008, 31 October); and joint physical custody. Although the Portuguese law does not contemplate this last regime, parents are sharing the residence with children between them, particularly those who attained high educational levels.…”
Section: The Portuguese Contextmentioning
confidence: 99%
“…As the younger generations and those in childrearing ages (30-44) tend to be more egalitarian than other age groups, they will support more strongly shared or better-conditions residence. Finally, as the older generations tend to be more supportive of the intensive mothering ideology (Ramos et al, 2019), they will show high levels of support to maternal residence (1b). ( 2) Following the hypothesis of the cultural double-bind of Portuguese society and the association between attitudes to DLF and the type of children's residence, we expect to find an attitudinal hybridization (different profiles) resulting from the combination of different attitudinal dimensions associated with DLF, parenting involvement and type of children's residence (multidimensionality) instead of a linear opposition between egalitarian and traditional profiles (unidimensional).…”
Section: The Portuguese Contextmentioning
confidence: 99%